TRANSFORMASI PEMBANGUNAN JALAN BARU, WISATA KAMPUNG NUSA, DAN PENGRAJIN MENDONG DALAM MENINGKATKAN EKONOMI DI PURBARATU, TASIKMALAYA - aji, dede; Mardani, Dede Aji; Imas Siti Masuroh (La Zhulma | Jurnal Ekonomi dan Bisnis Islam, 2025)
The construction of a new road in Purbaratu District, Tasikmalaya, represents a significant case for studying infrastructure's impact on local economies. This study examines how the new road affects local mendong handicraft artisans and roadside vendors. Using a mixed-method approach, the research finds that while accessibility has improved, the benefits have not been evenly distributed. Artisans face marketing and raw material supply challenges, while vendors struggle with spatial regulation and legality. The study highlights the necessity of zoning policies, digital adaptation training, and the development of community-based entrepreneurship ecosystems through multi-stakeholder collaboration. These findings underscore the need for synergy between physical infrastructure and socio-economic capacity building to ensure inclusive and sustainable development outcomes.